Exploring the Impact of Spiritual Tourism on Personal Transformation and Well-being: A Cross-cultural Analysis in the Sacred City of Haridwar - Ms. Megha Sharma,; Dr. Alka Maheshwari,; Dr. Swati Bisht, (The Bioscan, 2026)
This research delves into the transformative impact of spiritual tourism on personal development and well-being, focusing on the sacred city of Haridwar. Drawing on a mixed-methods approach, including qualitative interviews, surveys, and participant observations within the unique cultural context of Haridwar, the study aims to unravel the motivations, experiences, and perceived benefits of individuals engaging in spiritual tourism. Haridwar's rich cultural and religious heritage significantly shapes the spiritual tourism experience, fostering spiritual growth, self-discovery, and psychological well-being. Through a cross-cultural analysis, the research identifies commonalities and distinctions in the transformative journey across diverse backgrounds. The study also evaluates the economic and socio-cultural implications of spiritual tourism in Haridwar, considering both tourist and local community perspectives. This exploration is critical for understanding the delicate balance between economic benefits and the preservation of cultural integrity. By shedding light on the specific dynamics of spiritual tourism in Haridwar, this research contributes valuable insights to inform destination management strategies, promoting sustainable and culturally sensitive practices in spiritual tourism destinations.